Influence of local vibration on plasma creatine phosphokinase (CPK) activity. Issue 10 (October 1985) - Okada, A; Okuda, H; Inaba, R; Ariizumi, M
Abstract : This study was designed to obtain basic information about the mechanism of the occurrence of muscular disorders after exposure to vibration. The hind legs of rats were exposed to acute and chronic local vibration at frequencies of 30, 60, 120, 240, 480, and 960 Hz with a constant acceleration of 50 m/sec2. The exposure time was four hours for acute, and four hours a day for two weeks continuously for chronic exposure. Blood was collected after exposure to measure plasma creatine phosphokinase (CPK) activity. In both exposure groups the activity of plasma CPK was significantly higher at 30, 60, 120, 240, and 480 Hz compared with the control group and was especially high at 30 Hz; there was no significant change at 960 Hz. As a result of an analysis of the CPK isoenzymes, the increase in plasma CPK activity was shown to be due to the activity of the plasma CPK-MM fraction, originating in the skeletal muscle. Plasma CPK activity showed a tendency to decrease gradually with the increase in vibration frequency during acute exposure but showed no such tendency during chronic exposure. There was no remarkable pathohistological change in muscle preparations from the hind legs, hence it was presumed that the increase in plasma CPK activity was caused not by the morphological changes of muscle but by other mechanisms, such as an increase in the permeability of the cell membrane.